Reimagining Design Studios as Active Workspaces for Education 4.0: Collaborative and Flexible Learning Environments in Malaysian Higher Education - Awang, Arita Hanim; Razak, Rajabi Abdul; Jalil, Nurlelawati Ab; Rahman, Syakir Amir Ab; Denan, Zuraini (Tropical Scientific Journal, 2026)
Objective: The transformation of higher education in Malaysia towards Education 4.0 requires learning environments that foster creativity, collaboration, and adaptability. This study aims to reimagine the traditional design studio as an active workspace that integrates flexibility, inclusivity, and collaborative modes of learning. Research Method: The research adopts a qualitative design-based approach using conceptual modeling and computer-generated interior proposals. The study explores multiple spatial configurations that integrate individual, group, and hybrid learning zones inspired by co-working and contemporary workplace models. Findings: Findings reveal that reconfigurable studio layouts enhance collaboration and peer interaction while maintaining opportunities for focused individual work. Challenges include the potential loss of personalized space and the need for user adaptability to flexible layouts. Originality: This research introduces a design framework that aligns interior design pedagogy with Education 4.0 principles, fostering student-centered, technology-supported, and collaborative learning environments. It contributes to Malaysia’s Education 4.0 goals and supports SDG 4 (Quality Education), SDG 9 (Industry, Innovation, and Infrastructure), and SDG 11 (Sustainable Cities and Communities)